Pengembangan Model Penanaman Nilai-Nilai Karakter Pancasila Bermedia Wayang Suket Puspa Salira - Ramadhan, Rully Anas (Universitas Negeri Malang, 2022)
This study aimed to produce a feasible, attractive, and effective model for cultivating Pancasila character values with the media of Wayang Suket Puspa Salira. The research and development model used in this study referred to the steps of Borg & Gall. The test subjects in this study were seventh-grade students of SMP Diponegoro. The validity test results of material experts obtained an average of 91.6 percent, media experts at 95.8 percent, and lesson planning experts at 88.8 percent. The results of the small group trial obtained a pretest score of 62.67 and a post-test of 83.26, while the average score obtained from the large group trial was 65.76 pretest and 85.83 on the post-test. The test results showed increased student learning outcomes from the low to medium categories. This result indicated a significant change between learning outcomes before and after implementing the developed learning model.